From hybrid fibers to microfibers: the characteristics of polyamide 6/polypropylene blend via one-step twin-screw melt extrusion - Kunchimon, Siti Zaharah; Tausif, Muhammad; Goswami, Parikshit; Cheung, Vien (Wiley Online Library, 2020)
Multimaterial textiles are frequently employed to attain a certain function or aesthetic effect. The multimaterial assemblies face recycling limitations due to challenges to sort and separate the component materials. A one-step melt extrusion approach to process two mixed common textile polymers, polyamide 6 (PA6), and polypropylene (PP), into PA6:PP hybrid fibers is reported in this study. PA6:PP hybrid fibers were produced in four different configurations; PA6-50 (50 wt% PA6), PA6-60 (60 wt% PA6), PA6-65 (65 wt % PA6), and PA6-80 (80 wt% PA6). The PP component was sacrificially removed from the hybrid fibers and the resultant PA6 fiber structure was analyzed. The SEM images show the development of PA6 microfibers in PA6-50 and PA6-60 hybrid fibers with mean diameters of 0.76 μm and 1.13 μm upon fiber drawing, respectively. In PA6-65 hybrid fibers, the PA6 microfibers were found along with areas where PA6 was encapsulating the PP. Thermal and mechanical properties of the untreated and treated hybrid fibers were also investigated. PA6-60 hybrid fibers were processed into single jersey knitted fabrics and treated to obtain PA6 microfibers fabrics. The bursting strength and wicking properties of the fabric, before and after treatment, were comparatively studied. POLYM. ENG. SCI., 00:000–000, 2020. © 2020 Society of Plastics Engineers